KETERSEDIAAN JENIS PAKAN GAJAH SUMATERA (Elephas maximus sumateranus) DI AREAL HTI PT. RIMBA PERANAP INDAH - Kesi Elisabeth Silvania Siregar; Defri Yoza; Viny Volcherina Darlis (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Elephas maximus sumateranus are a type of animal whose food is mostly found in forest are as.      Elephas maximus sumateranus consume various types of plants and are needed in large quantities. PT. Rimba Peranap Indah have a protected area that has an ecological role for the flora and fauna in this area, including a habitat for elephant. This study aims to determine the type and availability of elephant feed in the concession area in the PT. Rimba Peranap Indah. The method used in this        research is direct and indirect survey methods. Sampling was carried out using path transects with the purposive sampling method. The result showed that the type of elephant feed in the concession area of PT. Rimba Peranap Indah were found as many as 42 species from 12 families, the dominant family found is the family Myrtaceae. The availability of food for elephant in the concession area of          PT. Rimba Peranap Indah are not sufficient. The area of the conservation area can only be sufficient for ± 20 elephants out of 40 elephants crossing the concession area of PT. Rimba Peranap Indah. Keywords : Elephas maximus sumateranus, habitat, feed